2014
DOI: 10.1002/ijc.29226
|View full text |Cite
|
Sign up to set email alerts
|

USP33 mediates Slit‐Robo signaling in inhibiting colorectal cancer cell migration

Abstract: Summary Originally discovered in neuronal guidance, the Slit-Robo pathway is emerging as an important player in human cancers. However, its involvement and mechanism in colorectal cancer (CRC) remains to be elucidated. Here, we report that Slit2 expression is reduced in CRC tissues compared with adjacent non-cancerous tissues. Extensive promoter hypermethylation of the Slit2 gene has been observed in CRC cells, which provides a mechanistic explanation for the Slit2 downregulation in CRC. Functional studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 39 publications
3
53
1
Order By: Relevance
“…The role of Slit-Robo and its functions in cancer treatment and development are becoming increasingly unraveled but also increasingly complex. Consistent with in colorectal cancer and breast cancer [18, 19], our results showed that USP33 can function by interacting with Robo1 in PTC cells, which may enhancing the Slit-Robo signaling and thus inhibit tumor progression. Furthermore, our data suggested that USP33 can activate caspase 9 and caspase 3 proteins, in accordance with the fact that Robo1 functions partly by inducing cell apoptosis [26].…”
Section: Discussionsupporting
confidence: 72%
“…The role of Slit-Robo and its functions in cancer treatment and development are becoming increasingly unraveled but also increasingly complex. Consistent with in colorectal cancer and breast cancer [18, 19], our results showed that USP33 can function by interacting with Robo1 in PTC cells, which may enhancing the Slit-Robo signaling and thus inhibit tumor progression. Furthermore, our data suggested that USP33 can activate caspase 9 and caspase 3 proteins, in accordance with the fact that Robo1 functions partly by inducing cell apoptosis [26].…”
Section: Discussionsupporting
confidence: 72%
“…Although the importance of some members of the USP family in a variety of biological processes [29], such as regulation of DNA damage checkpoint response, epigenetic regulation and protein stabilization is well established, very little is known about the biological function of the majority of the USPs. Here, we revealed that USP47 is a direct target of miR-204-5p in GC and knockdown USP47 expression could Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of USP33 has been investigated in breast, colon and lung cancer cells. USP33 can inhibit the migration of these cells by its deubiquitinating activity on Robo [38][39][40]. Here, we found that USP33 could deubiquitinate and stabilize PPM1A (Fig.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 64%